Methods for Quantifying Neurotransmitter Dynamics in the Living Brain With PET Imaging - Ceccarini, Jenny; Liu, Heather; Van Laere, Koen; Morris, Evan D.; Sander, Christin Y. (Frontiers in Physiology, 2020)
PET neuroimaging in neuropsychiatry is a powerful tool for the quantification of molecular brain targets to characterize disease, assess disease subtype differences, evaluate short and long-term effects of treatments, or even to measure neurotransmitter levels in healthy and psychiatric conditions. In this work, we present different methodological approaches (time-invariant models and models with time-varying terms) that have been used to measure dynamic changes in neurotransmitter levels induced by pharmacological or behavioural challenges in humans. The developments and potential use of hybrid PET/MRI for neurotransmission brain research will also be highlighted.